Modeling dependencies in finance using copulae - Wolfgang Karl Härdle; Ostap Okhrin; Yarema Okhrin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
In this paper we provide a review of copula theory with applications to finance. We illustrate the idea on the bivariate framework and discuss the simple, elliptical and Archimedean classes of copulae. Since the copulae model the dependency structure between random variables, next we explain the link between the copulae and common dependency measures, such as Kendall's tau and Spearman's rho. In the next section the copulae are generalized to the multivariate case. In this general setup we discuss and provide an intensive literature review of estimation and simulation techniques. Separate section is devoted to the goodness-of-fit tests. The importance of copulae in finance we illustrate on the example of asset allocation problems, Value-at-Risk and time series models. The paper is complemented with an extensive simulation study and an application to financial data.
Keywords: C00; C14; C51; 330; Distribution functions; dimension reduction; risk management; statistical models; Finanzmarkt; Kopula (Mathematik); Statistische Verteilung; Portfolio-Management; Value at Risk; Risikomanagement; Zeitreihenanalyse; Theorie